Mass transfer intensification of CO2 absorption in monoethanolamine using high frequency ultrasonic technology in continuous system - Yusof, S.M.M. (Elsevier Ltd, 2020)
Intensification technology for absorption process is of interest for the separation of CO2 from natural gas in the offshore. High frequency ultrasonic absorption technology in batch system has shown remarkable potential for offshore application due to high operating flexibility and mass transfer performance. Therefore, in this work, a high frequency ultrasonic absorption (HiFUA) of CO2 from natural gas using monoethanolamine is proposed for continuous system to suit the industrial mode of operation. The effect of the operating parameters on the overall mass transfer coefficient was investigated, thus the optimum condition was identified using central composite design coupled with response surface methodology. Based on the results, the optimum condition was found at the gas flow rate of 30 SLPM, liquid flow rate of 0.15 SLPM, pressure of 10 bar and ultrasonic voltage of 30 V, which resulted to maximum mass transfer coefficient of 268.9 mol/kPa.m3.hr. The presence of high frequency ultrasonic irradiation has enhanced the absorption process 7 times higher as compared to the case of without ultrasonic irradiation due to its physical effects which are the acoustic streaming, fountain and atomization. The enhancement in continuous system is lower than the batch system reported in the literature due to the difference in the reactor configuration. Nevertheless, HiFUA has intensified the mass transfer performance 12 times higher as compared to conventional packed bed column for CO2-MEA system. This work has shown great potential of high frequency ultrasonic irradiation as an intensification technology for CO2 absorption process. Â© 2020 Elsevier Ltd